ENERGY CHARACTERISTICS OF BRUSHLESS MAGNETOELECTRIC MOTORS OF THE RETURN-ROTARY MOTION - K.P. Akinin; V.G. Kireyev; A.A. Filomenko; O.V. Vertelieva (Праці Інституту електродинаміки Національної академії наук України, 2022)
The paper presents the results of studies of the structure of the powers that characterize the state of a specialized brush-less magnetoelectric motor of return-rotary motion. The calculated curves of the rotor angular speed, the motor torque and the torques of mechanical resistance, and the curves of the instantaneous values of powers of consumption, useful mechanical load, and losses are given. The frequency dependences of the efficiency factor and power components are obtained based on their calculation. Ref. 7, fig. 5.